Pengaruh Kompetensi, Motivasi dan Budaya Organisasi terhadap Kinerja Tridharma Dosen dengan Komitmen sebagai Variabel Moderasi - Jamil, Rudi; Mutmainah, Isbandriyati; Yulia, Iis Anisa (Jurnal EMT KITA, 2026)
This study aims to examine and analyze the influence of competence, motivation, and organizational culture on the performance of lecturers’ Tridharma with commitment as a moderating variable. This study used all 108 state lecturers (ASN) at the Faculty of Forestry and Environment, IPB University as respondents. Data were collected by distributing questionnaires to all respondents. The analytical method used was multiple linear regression to examine the influence of competence, motivation, and organizational culture on the performance of lecturers’ Tridharma and Moderating Regression Analysis (MRA) to examine the ability of the commitment variable to moderate the influence of competence, motivation, and organizational culture on the performance of lecturers’ Tridharma. The results of the multiple linear regression analysis showed that competence, motivation, and organizational culture significantly influenced the performance of lecturers’ Tridharma both partially and simultaneously. The results of the MRA analysis showed that the commitment variable significantly influenced the performance of lecturers’ Tridharma and was able to moderate the influence of competence and motivation on the performance of lecturers’ Tridharma, but was unable to moderate the influence of organizational culture on the performance of lecturers’ Tridharma.